Envisioning the Potential of 6G Use Cases—A Dual Perspective of Innovation and Business - Muhua Wei; Jun Wu; Huili Liu; Lin Lin; Zheng Zhang; Mayuan Sun (IEEE Access)
Currently, 6G technology is at a pivotal stage for research and standardization, with the next three to five years being crucial for achieving technological breakthroughs and fostering industrial development. 6G is anticipated to support a broader spectrum of application scenarios, lead us into a more intelligent and interconnected future. The applications and use cases of 6G serve as a vital link between technological innovation and user demands, laying the groundwork for key network performance indicators, functional design, and service capability planning, and paving the way for its future commercialization. The forward-looking exploration and identification of potential 6G use cases, particularly those with high development prospects, can offer strategic guidance for technological research and development. This study introduces an innovative 6G Use Case Potential Matrix, designed from dual perspectives of innovation and business viability. It assesses application innovation through the volume and trends of invention patents and evaluates business potential using market outlook analyses. Based on these insights, typical 6G use cases are categorized into four groups: leading use cases, use cases to be broken through, use cases to be excavated, and use cases to be cultivated. We select 23 typical 6G use cases with consensus for empirical analysis, and recommendations for the development and layout of 6G use cases are given. The findings of this research aim to offer fresh perspectives for the systematic planning of 6G applications development pathways and to support decision-making on aligning technology research directions with network requirements definitions.